2020
DOI: 10.1111/jfs.12783
|View full text |Cite
|
Sign up to set email alerts
|

Food safety risk posed to consumers of table eggs from layer farms in Gauteng Province, South Africa: Prevalence of Salmonella species and Escherichia coli, antimicrobial residues, and antimicrobial resistant bacteria

Abstract: The study conducted on 39‐layer farms in Gauteng Province, South Africa determined the prevalence and resistance of enteropathogens, and antimicrobial residues in table eggs collected from the farms. Eggs were tested for the presence of bacteria using standard methods. The resistance of bacteria to eight antimicrobial agents was determined using the disc diffusion method. Antimicrobial residues were detected in table eggs using the microbial inhibition test, enzyme‐linked immunosorbent assay (ELISA), and high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 46 publications
(102 reference statements)
0
3
2
Order By: Relevance
“…This study found only aminoglycoside and tetracycline residues in the eggs (in both albumen and yolk). The prevalence of tetracycline residues found in this study was higher than that in the study performed by Adesiyun et al [11]. In contrast, our finding was lower than that in the report by Adesiyun et al [28].…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…This study found only aminoglycoside and tetracycline residues in the eggs (in both albumen and yolk). The prevalence of tetracycline residues found in this study was higher than that in the study performed by Adesiyun et al [11]. In contrast, our finding was lower than that in the report by Adesiyun et al [28].…”
Section: Discussioncontrasting
confidence: 89%
“…The prevalence of Salmonella in the eggs in the present study was lower than that found in the results of Camba et al [10]. The Salmonella prevalence in the ESM eggshells in our study was higher than that found in the report of Adesiyun et al [11] (7.7%) and Camba et al [10] (0.06 %). Contaminated eggshells can cause human salmonellosis by consuming raw or undercooked eggs that lack shell-cleaning or are stored at temperatures above room temperature (30 o C) for more than 3 weeks.…”
Section: Discussioncontrasting
confidence: 76%
“…The resistance of bacteria to tetracycline in South Africa has been attributed to the unregulated use of veterinary drugs, including tetracycline, in the country. This is attributed to the existing Fertilizers, Farm, and Agricultural and Stock Remedy Act (Act 36, 1947), which legalizes the use of certain antimicrobial agents, such as sulphonamides and trimethoprim, to be purchased over-the-counter, and they are used for treatment and as growth promoters [ 70 ]. Interestingly, the phenotypic resistance exhibited to tetracycline (36.8%) determined by Gana [ 37 ] correlates well with the putative resistance to tetracycline due to both tet ( M ) and tet(S ) genes based on WGS on the same isolates, suggesting that the genes may have been partly responsible for the resistance detected.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been conducted on related contamination of eggs caused by Salmonella spp. and E. coli [15,16]; however, S. aureus infection in eggs in Indonesia has yet to be studied intact and is only limited in prevalence. This review aimed to describe the incidence of S. aureus and methicillin-resistant Staphylococcus aureus (MRSA) in Indonesia compared with that in several other countries, as well as One Health approach to the prevention and control of S. aureus contamination of eggs in Indonesia.…”
Section: Introductionmentioning
confidence: 99%